Phytochemical screening and Total Phenolics of Stem and Leaf extracts of Sandoricum koetjape - Susy Saadah; Silvester Maximus Tulandi (Universitas Djuanda, 2020)
Sandoricum koetjape belongs to the family Meliaceae which is known to have antioxidant activity. Natives of Betawi use stem of S. koetjape for the treatment of helminthiasis meanwhile leaf of S. koetjape was used for the treatment of fever. Stem and leaf of that plant were tested for phytochemical and total phenolics content. Phytochemical screening of plants extracts revealed the presence of quinon. Quantitative determination of total phenolics of methanol and chloride acid extract was carried out using colorimetric methods. The mean total phenolics content was found to be 1.4155 mg/g and 3.1469 mg/g for stem and leaf respectively (ANOVA, p=0.000). There is significant difference in total phenolics content between the stem and leaf of Sandoricum koetjape.